From bad to worse: when lung cancer complicates idiopathic pulmonary fibrosis1. Issue 4 (14th February 2018) - Strock, Stephen B; Alder, Jonathan K; Kass, Daniel J
Abstract: Patients with idiopathic pulmonary fibrosis have a significantly increased risk for the development of lung cancer. The morbidity and mortality of this disease combination are substantial, and, unfortunately, there are currently few data to help guide clinicians in its diagnosis and treatment. In a recent issue of this journal, Hwang et al presented one of the first studies to evaluate lung cancer in patients with idiopathic pulmonary fibrosis at the molecular level. They demonstrate variants in regulators of the cell cycle, which are known to be important in malignant transformation and may also be important in the pathogenesis of idiopathic pulmonary fibrosis. Further understanding of the pathogenic overlap between lung cancer and idiopathic pulmonary fibrosis could help point the direction to specific diagnostic modalities and targeted treatment of both conditions in the future. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd. Abstract : Linked Article: Hwang et al. J Pathol 2018; DOI:244: 25‐35